2007
DOI: 10.1002/anie.200703000
|View full text |Cite
|
Sign up to set email alerts
|

From 2,4‐Diphospha‐3‐Thia‐ and ‐3‐Selenapentadienes [(Me3Si)2CP]2E to Heteronorbornane Cage Compounds

Abstract: Highly unsaturated organophosphorus compounds are rich in energy, and tend to rearrange to more stable rings, cages, and polymers. Nieckes 2,3,4-triphosphapentadienide anion [{(Me 3 Si) 2 C = P} 2 P] À (1), [1] the only p-donor heteroatombridged bisphosphaalkene anion that allows electronic communication between the neighboring P=C bonds, is known to undergo thermal elimination/re-addition reactions to furnish anionic P 3 C 2 heterocyles, [1] but its synthetic potential remains unexplored. The uncharged isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently it was observed that 1a and 1b add elemental sulfur and selenium in a surprising way, different from the behavior of comparable monofunctional phosphaalkenes. 2 In the following, we report our first experiments on reactions of 1a and 1b with cyclopentadiene and with tetrachloro-o-benzoquinone (TOB), both of which are typical reagents for [2+4] cycloadditions to phosphaalkenes. [3][4][5] TOB also adds oxidatively to other shortlived or persistent compounds of low-coordinated phosphorus, [6][7][8] and-in a [4+1] fashion-to P(σ 3 λ 3 )-compounds, 6,[9][10][11][12] 2 C=P-E-PR 2 (R = tBu, iPr) with cyclopentadiene, the initially formed endo-isomers usually rearranged to the more stable exo-isomers within 24 h 4 ; we therefore assume that both diastereomers of 2a and 2b were isolated as the exo,exo-isomers, as depicted in Scheme 1.…”
Section: Diastereoselective Reactions Of Sulfur-and Selenium-bridged mentioning
confidence: 99%
“…Recently it was observed that 1a and 1b add elemental sulfur and selenium in a surprising way, different from the behavior of comparable monofunctional phosphaalkenes. 2 In the following, we report our first experiments on reactions of 1a and 1b with cyclopentadiene and with tetrachloro-o-benzoquinone (TOB), both of which are typical reagents for [2+4] cycloadditions to phosphaalkenes. [3][4][5] TOB also adds oxidatively to other shortlived or persistent compounds of low-coordinated phosphorus, [6][7][8] and-in a [4+1] fashion-to P(σ 3 λ 3 )-compounds, 6,[9][10][11][12] 2 C=P-E-PR 2 (R = tBu, iPr) with cyclopentadiene, the initially formed endo-isomers usually rearranged to the more stable exo-isomers within 24 h 4 ; we therefore assume that both diastereomers of 2a and 2b were isolated as the exo,exo-isomers, as depicted in Scheme 1.…”
Section: Diastereoselective Reactions Of Sulfur-and Selenium-bridged mentioning
confidence: 99%
“…Du Mont et al reported that reaction of {(Me 3 Si) 2 CQP} 2 E (E = S, Se) with elemental S or Se generates a heteronorbornane cage compound (below left). 47 Reversible chalcogen exchange is observed and excess sulfur leads to sequential oxidation of the P III centre (below centre and right).…”
Section: Chalcogen-phosphorus Compoundsmentioning
confidence: 99%
“…In general, the oxi-dation of diphosphenes with elemental sulphur (or selenium) is the most established route to synthesize P 2 Ch (Ch = S, Se) rings (Scheme 3). [58][59][60][61][62][63][64][65][66] A handful of other routes have also been reported, [67][68][69][70][71] among them a combined dechlorinationelementation strategy using (Me 3 Sn) 2 E and (tBuPCl) 2 to access (tBuP) 2 E (E = S, Se) (Scheme 3, middle). 72 In here we show that Scheme 2 Phospha-Wittig reagents as phosphinidene precursors and their diverse reactivity toward selected nucleophiles.…”
Section: Introductionmentioning
confidence: 99%